Thermal stability study of transition metal perovskite sulfides - Niu, Shanyuan; Milam-Guerrero, JoAnna; Zhou, Yucheng; Ye, Kevin; Zhao, Boyang; Melot, Brent C.; Ravichandran, Jayakanth (Journal of materials research, 2018)
Transition metal perovskite chalcogenides, a class of materials with rich tunability in functionalities, are gaining increased attention as candidate materials for renewable energy applications. Perovskite oxides are considered excellent n-type thermoelectric materials. Compared to oxide counterparts, we expect the chalcogenides to possess more favorable thermoelectric properties such as lower lattice thermal conductivity and smaller band gap, making them promising material candidates for high temperature thermoelectrics. Thus, it is necessary to study the thermal properties of these materials in detail, especially thermal stability, to evaluate their potential. In this work, we report the synthesis and thermal stability study of five compounds, α-SrZrS3, β-SrZrS3, BaZrS3, Ba2ZrS4, and Ba3Zr2S7. These materials cover several structural types including distorted perovskite, needle-like, and Ruddlesden–Popper phases. Differential scanning calorimeter and thermogravimetric analysis measurements were performed up to 1200 °C in air. Structural and chemical characterizations such as X-ray diffraction, Raman spectroscopy, and energy dispersive analytical X-ray spectroscopy were performed on all the samples before and after the heat treatment to understand the oxidation process. Our studies show that perovskite chalcogenides possess excellent thermal stability in air at least up to 550 °C.